Social development issues - Inter-University Consortium for International Social Development (Lyceum Books, 2004)
Published by: Inter-University Consortium for International School Development in cooperation with the Center for Social Development - George Warren Brown School of Social Work - Washington University in St. Louis; Neal A. Newfield, Ph.D., LICSW (Giver)